2018
DOI: 10.1007/s00270-018-1959-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency and Microwave Ablation Compared to Systemic Chemotherapy and to Partial Hepatectomy in the Treatment of Colorectal Liver Metastases: A Systematic Review and Meta-Analysis

Abstract: PurposeTo assess safety and outcome of radiofrequency ablation (RFA) and microwave ablation (MWA) as compared to systemic chemotherapy and partial hepatectomy (PH) in the treatment of colorectal liver metastases (CRLM).MethodsMEDLINE, Embase and the Cochrane Library were searched. Randomized trials and comparative observational studies with multivariate analysis and/or matching were included. Guidelines from National Guideline Clearinghouse and Guidelines International Network were assessed using the AGREE II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
142
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(149 citation statements)
references
References 74 publications
2
142
1
4
Order By: Relevance
“…Prior reports have noted extremely well-defined, well-demarcated zones of ablation, based upon limited energy penetration. Thus, although these attributes of laser ablation may not be ideal for the treatment of liver metastases and have led to greater adoption of other energy sources in the liver [21][22][23][24], these very properties are likely to be more suited for parathyroid pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports have noted extremely well-defined, well-demarcated zones of ablation, based upon limited energy penetration. Thus, although these attributes of laser ablation may not be ideal for the treatment of liver metastases and have led to greater adoption of other energy sources in the liver [21][22][23][24], these very properties are likely to be more suited for parathyroid pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical benefits of MWA over RFA include larger ablation zone, shorter duration, and no heat‐sink effect . There are some studies reporting the outcomes of MWA for colorectal liver metastases as a safe and effective modality for use in the treatment of CRLM patients . Correa‐Gallego et al.…”
Section: Specific Techniques To Increase Resectabilitymentioning
confidence: 99%
“…6 Several uncontrolled studies of TA have reported OS outcomes similar to those after surgical resection (up to 55% at 5 years). [7][8][9][10] Different TA technologies are available including radiofrequency ablation (RFA), microwave ablation (MWA), laser, and cryoablation. They all use either heat or freezing temper-atures as a mean to achieve cell damage and death of the target tumor.…”
mentioning
confidence: 99%